Mapping of Seismic Vulnerability Potential for Earthquake Disaster Migitation in South Morotai: Pemetaan Potensi Kerentanan Seismik sebagai Mitigasi Bencana Gempa di Morotai Selatan - Rohima Wahyu Ningrum; Risky Nuri Amelia; Suryani Taib; Rahim Achmad; Marwis Aswan (JURNAL GEOCELEBES, 2022)
The geological condition of Morotai Island is influenced by small faults and tectonic activity from several major and minor plates that form the subduction zone, are the Pacific plate, the Philippine plate, the Sangihe plate, and the Moluccas Sea plate. This causes Morotai Island to have a high potential for earthquake hazards. South Morotai is the center of government, services, trade and economy on Morotai Island, and has a high potential for earthquakes. Therefore, an analysis of the distribution of seismic vulnerability values ​​in South Morotai was carried out based on mapping as a disaster mitigation effort in South Morotai. The microtremor method uses the H/V spectral ratio analysis technique to analyze the level of earthquake hazard based on the value of the seismic vulnerability index by considering local soil conditions. The ground frequency value (f0) obtained when measuring microtremor is between 0.6 Hz to 0.7 Hz. The amplitude value (A0) in the South Morotai area is around 1.9 – 5.2 times strengthening. The value of the seismic susceptibility index (Kg) in the study area is calculated based on the value of the basic frequency and amplitude with between 5.9 to 44.8. It was concluded that the distribution of a high Kg index and an earthquake prone area was in Darame Village, Muhajirin Village, and Wawama Village with a Kg value > 20. This area is composed of alluvium consisting of gravel, potential mud, and boulders, so it is classified into soft soil type. Less vulnerable areas are in Gotalamo Village, Daruba Pantai Village, and Darame Village